Acquisition announcement and stock price behaviour: the Malaysian experience - Fauzias Mat Nor (Penerbit Universiti Kebangsaan Malaysia, 1993)
This paper examines the effects of acquisition announcement on the price behaviour of the Malaysian bidders and target firms. Event study technique is the method used to compute abnormal returns, based on the single index or market model. However, two other models, the capital asset pricing model (CAPM) with unconstrarned and constrarned intercept, and the market model with constrained parameters a = O and p = 1 are also included in this study to ascertain whether the specificatzon of control returns effect the results. There are no obvious difference in the conclusions from using diferent models.